2015
DOI: 10.4037/ajcc2015320
|View full text |Cite
|
Sign up to set email alerts
|

Body Temperature and Mortality in Patients with Acute Respiratory Distress Syndrome

Abstract: Background Little is known about the relationship between body temperature and outcomes in patients with acute respiratory distress syndrome (ARDS). A better understanding of this relationship may provide evidence for fever suppression or warming interventions, which are commonly applied in practice. Objective To examine the relationship between body temperature and mortality in patients with ARDS. Methods Secondary analysis of body temperature and mortality using data from the ARDS Network Fluid and Cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 35 publications
5
19
4
2
Order By: Relevance
“…Thus, lowering the VO 2 [56,57] should be considered throughout early severe ARDS from acute cardio-ventilatory distress well into stabilization and weaning. This recommendation contrasts with the observation that a high fever in ARDS patients is associated with higher survival [60]. Possibly, patients with elevated temperatures [60] present with a high sympathetic activity and withstand major sickness].…”
Section: Pressure Support [Ps])]contrasting
confidence: 44%
See 1 more Smart Citation
“…Thus, lowering the VO 2 [56,57] should be considered throughout early severe ARDS from acute cardio-ventilatory distress well into stabilization and weaning. This recommendation contrasts with the observation that a high fever in ARDS patients is associated with higher survival [60]. Possibly, patients with elevated temperatures [60] present with a high sympathetic activity and withstand major sickness].…”
Section: Pressure Support [Ps])]contrasting
confidence: 44%
“…This recommendation contrasts with the observation that a high fever in ARDS patients is associated with higher survival [60]. Possibly, patients with elevated temperatures [60] present with a high sympathetic activity and withstand major sickness].…”
Section: Pressure Support [Ps])]contrasting
confidence: 44%
“…administration of LPS induces severe lung injury, with characteristic symptoms of ALI, including excessive leukocyte accumulation, pulmonary edema, and intrapulmonary hemorrhage. ALI induced a persistent reduction of body weight and body temperature, which is known to be related to ARDS clinical outcomes . Melatonin significantly ameliorated the above symptoms, and pulmonary‐targeted melatonin provided the maximal protective effects against ALI.…”
Section: Discussionmentioning
confidence: 98%
“…However, another study on patients with acute respiratory distress syndrome reported contradictory results that fever in early phase may be an important factor in determining favorable outcome (21). Thus, the aim of our present study was to evaluate the association of body temperature with MV duration in a heterogenous cohort of mechanically ventilated patients.…”
Section: Introductionmentioning
confidence: 99%